KAMPANYE CEGAH STUNTING, BANGSA SEHAT SEJAHTERA - Tri Siswati; Yustiana Olfah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2020)
According to Riskesdas2018, 3 out of 10 toddlers suffer from stunting. Stunting in early in later life periods in childhood, adolescence, adulthood, and the elderly. Stunting hthe form of low learning achievement and reduced opportunities to get a good school. In a 22% reduction in the chance of getting good jobs compared to normal adults and metabolic syndrome is higher than normal adults. While short adolescents will gro consequences including giving birth to low birth weight babies and short, and the caesar (SC) is higher because of